Da maik da āzādạy pah silsilah kṣhi da Rūsī Turkistān aw Afghānistān safar - Akbar, ʻAbd al-Akbar Khān, b. 1899 (Akbar Buk Sṭāl, 1968)
Author's travel experiences in Afghanistan and Russian Turkestan as a student leader in the Indian freedom movement; v. 1: 1920-22; includes a sociopolitical study of India and Afghanistan of that period.